Malignant peripheral nerve sheath tumours: an outcome analysis of 32 patients in Lerdsin Hospital, Thailand - Goh, Kian Liang; Kiatisevi, Piya; Sukanthanak, Bhasanan; Piakong, Pongsiri (ResearchOne Publishing House, 2018)
Background Malignant peripheral nerve sheath tumours (MPNST) are rare soft tissue sarcoma which exhibit a biologically aggressive behaviour with propensity for rapid progression and high mortality rate. Currently, the data for this tumour is lacking especially with regards to the Asian population.